Air-sea coupling influence on projected changes in major Atlantic hurricane events - Derrick K. Danso; Christina M. Patricola; Jaison Kurian; Ping Chang; Philip Klotzbach; I.-I. Lin (Weather and Climate Extremes, 2024)
Tropical cyclone (TC) projections with atmosphere-only models are associated with uncertainties due to their inability to represent TC-ocean interactions. However, global coupled models, which represent TC-ocean interactions, can produce basin-scale sea surface temperature biases in seasonal to centennial simulations that lead to challenges in representing TC activity. Therefore, focusing on recent individual major hurricane events, we investigated the influence of TC-ocean coupling on the response of TCs to anthropogenic change using atmosphere-only and coupled atmosphere-ocean regional model simulations. Under an extremely warm scenario, coupling does not influence the signs of projected TC rainfall and intensity responses. Coupling, however, does influence the magnitude of projected intensity and especially rainfall. Within a 500 km radius region of the TCs, the projected rainfall increases in coupled simulations are 3–59 % less than in the atmosphere-only simulations, driven by enhanced TC-induced sea surface temperature cooling in the former. However, the influence of coupling on the magnitude of projected rainfall could vary considerably over the regions of highest rainfall generated by TCs.